A new species of Chileotrecha Maury, 1987 (Solifugae: Ammotrechidae) from Argentina with notes on the genus - Iuri, Hernán (2014)
The monotypic genus Chileotrecha Maury, 1987, includes Chileotrecha atacamensis Maury, 1987 from Atacama and Coquimbo regions in Chile. We describe Chileotrecha argentinensis n. sp., which is the first record of the genus from Argentina. Phylogenetic relationships of Chileotrecha with other genera of Ammotrechidae are discussed based on external morphology. We report for the first time the presence of blunt and clubbed setae in Ammotrechidae. We also report for the first time the presence of two pairs of microsetae in the posterior margin of genital plate and in the posterior margin of spiracular sternites I and II, and the presence of a single microseta on each side of postspiracular sternite I.